(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article proposes to establish direct relations between Merleau-Ponty’s phenomenology, more specifically with the notion of chiasma, and the theatrical scenic space, through the review of some authors and some scenic situations thought especially for such relations. Based on philosophical notions, with examples commented by Merleau-Ponty, such as the relationship between figure and background, for example, we consider the importance of the viewer’s point of view, taken as an element of effectuation of the phenomenological problem, since the relation of the spectacle with the viewer is a founding element of contemporary theatrical poetics.